PENGARUH MOTIVASI KERJA DAN BEBAN KERJA TERHADAP KEPUASAN KERJA PEGAWAI BADAN PENGELOLAAN KEUANGAN DAN ASET DAERAH (BPKAD) KOTA BIMA - M. Al-jihad; Jaenab (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2021)
This study aims to determine the effect of work motivation and workload on job satisfaction of employees of the Regional Financial and Asset Management Agency (BPKAD) in Bima City. This research uses associative research with a quantitative approach. For sampling technique (purposive sampling) was used by determining the sample as respondents were all 76 the State Civil Service (ASN) employees in the office of the Regional Financial and Asset Management Agency (BPKAD) Bima City. Data collection techniques using observations, questionnaires (questionnaires) with a Likert scale. Technical Analysis using Validity Test, Reliability Test, Classical Assumption Test which consists of: Normality Test, Multicollinearity Test, Test, Heteroscedasticity and Autocorrelation Test. Multiple linear regression analysis, coefficient test, multiple correlation, determination coefficient test (R2), partial test (T test), simultaneous test (F test). The results showed that motivation has a significant effect on employee job satisfaction, work load has a significant effect on employee job satisfaction, motivation and workload has a significant effect on employee job satisfaction.